Multimodel climate and variability of the stratosphere - Butchart, Neal; Charlton-Perez, A.J.; Cionni, Irene; Haynes, P.H.; Hardiman, S.C.; Krüger, K.; Kushner, P.; Newman, P.A.; Osprey, S.M.; Perlwitz, J.; Sigmond, M.; Wang, L.; et al. (Journal of Geophysical Research, 2011)
The stratospheric climate and variability from simulations of sixteen chemistryclimate models is evaluated. On average the polar night jet is well reproduced though its variability is less well reproduced with a large spread between models. Polar temperature biases are less than 5 K except in the Southern Hemisphere (SH) lower stratosphere in spring. The accumulated area of low temperatures responsible for polar stratospheric cloud formation is accurately reproduced for the Antarctic but underestimated for the Arctic. The shape and position of the polar vortex is well simulated, as is the tropical upwelling in the lower stratosphere. There is a wide model spread in the frequency of major sudden stratospheric warnings (SSWs), late biases in the breakup of the SH vortex, and a weak annual cycle in the zonal wind in the tropical upper stratosphere. Quantitatively, Ã¢ÂÂmetricsÃ¢ÂÂ indicate a wide spread in model performance for most diagnostics with systematic biases in many, and poorer performance in the SH than in the Northern Hemisphere (NH). Correlations were found in the SH between errors in the final warming, polar temperatures, the leading mode of variability, and jet strength, and in the NH between errors in polar temperatures, frequency of major SSWs, and jet strength. Models with a stronger QBO have stronger tropical upwelling and a colder NH vortex. Both the qualitative and quantitative analysis indicate a number of common and longÃ¢ÂÂstanding model problems, particularly related to the simulation of the SH and stratospheric variability.